"The more Postpone, The more Alone? Analysis The Relationship Between Procrastination and Loneliness in College Students - Nayla Maghfirohtul Mas Ula (Glosains: Jurnal Sains Global Indonesia, 2025)
University students are in early adulthood, a developmental stage characterized by increasing academic and social demands. These demands often lead to procrastination, defined as the tendency to delay academic tasks, which May affect psychological well-being, including feelings of loneliness. This study aimed to analyze the relationship between procrastination and loneliness among university students. This research employed a quantitative approach with a correlational design. The participants were selected using convenience sampling, with 79.1% female and 20.9% male respondents. Data were collected using Likert-scale questionnaires that have been tested for validity and reliability. Data analysis was conducted using Pearson correlation with the assistance of SPSS software. The results indicated a positive and significant relationship between procrastination and loneliness among university students, suggesting that higher levels of procrastination are associated with higher levels of loneliness. These findings are expected to contribute to the development of academic and psychological interventions aimed at reducing procrastination and enhancing students' social well-being.